Direct and indirect crisis of food security due to COVID-19 emergence in Addis Ababa and Amhara regions, Ethiopia: a lesson for the inevitable pandemics - Daniel Teshome Gebeyehu; Leah East; Stuart Wark; Md Shahidul Islam (BMC Public Health)
Abstract Background COVID-19 caused a significant impact on food security; particularly among low- and middle-income countries. The objective of the current study was to assess both the direct and indirect impact of COVID-19 on individuals’ food security in the metropolitan and regional context of Ethiopia. Methods This project utilized a retrospective study design with a mixed methods approach. It assessed the food insecurity experience of individuals both before and after the emergence of COVID-19 through the Food Insecurity Experience Scale (FIES). Food sellers were interviewed to identify the factors that increased post-COVID-19 emergence food insecurity. Inferential analysis using ordinal logistic regression was undertaken based on the Polytomous Universal Model (PLUM) procedure. Results The size of the family and the type of work for income generation were statistically associated (p < 0.05) with the food security of individuals, both before and after COVID-19 emergence. Location (p = 0.002, odds = 0.37), age (p = 0.002, odds = 2.57) and educational status (p = 0.001, odds = 0.24/) of individuals had a statistically significant effect on the food security of individuals before COVID-19 emergence only. The ordinal value of all FIES indicators increased after COVID-19 emergence compared with pre-pandemic food insecurity. Overall food security of individuals was reduced by 21.5%, with the moderate and severe food insecurity of individuals increasing by 13.1% and 15.9%, respectively. The COVID-19 preventive measures that affected the individuals’ food security, in the order of their priority, were: transport bans; food price increment; lockdown measures; job loss; market bans; social distance restrictions; fear of the pandemic; movement restrictions; over-buying; food inaccessibility; and, lack of cash due to bank closure. In addition, pre-existing non-pandemic related natural and man-made disasters played a role in the food security crisis, including drought, war, and desert locust emergence. Conclusion The COVID-19 pandemic has directly and indirectly affected individuals' food security. Learning from the experiences of COVID-19 may assist governments in preparing for future pandemics. Suggested improvements include forming impact reduction task forces and establishing disease prevention strategies that will not compromise food security.